VD_FINDINFO Séquestre / 2016 / 6 vom 25. Februar 2016 - VD Tribunal cantonal (2016)
SÉQUESTRELP, CESSION DE CRÉANCECO, PREUVE FACILITÉE, SUCCESSION, DETTE | 603 al. 1 CC, 164 al. 1 CO, 169 CO, 272 al. 1 ch. 1 LP, 278 al. 3 LP